Cover, Content, and Editorial Note from Borneo J Pharm Vol. 2 No. 2 November 2019 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published at November 2019. Starting from this edition, Borneo J Pharm make changes to the template in the article that will be published. The amendment aims to make it easier for readers to observe essential parts of each page of the article. The aim of this journal is to publish high-quality articles dedicated to all aspects of the latest outstanding developments in the field but not limited to Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, Clinical-Community Pharmacy, Management Pharmacy, and other Pharmacy aspects. This edition contains 13 articles consisting of Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, and Clinical-Community Pharmacy topics. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition on May 2020